A Case Study on the Utilization of Teachy for Assessing Grammar Mastery in Senior High School - Mada Gymnastiar Andy Nugraha; Fadhilawati, Dian; Nita Sutanti (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This study explores the use of the Teachy application to enhance grammar assessment among eleventh-grade students at SMAN 1 Blitar. Addressing the limitations of traditional paper-based tests, this qualitative single-case study involved one English teacher and five students selected through purposive and snowball sampling. Data were collected through interviews, classroom observations, and document analysis, and analyzed using Miles and Huberman’s interactive model combined with grounded theory coding. The findings indicate that Teachy supports effective planning, implementation, and evaluation of grammar assessment; aligns with curriculum objectives and Bloom’s Taxonomy; and provides instant feedback. Despite challenges related to internet access, device availability, and digital skills, Teachy increased student engagement and interactivity in grammar learning.